Cloud Based Peer-to-Peer Sharing Resource - Saidatul Huda, A Samrin (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Cloud based file sharing is quickly gaining in popularity. File sharing is used as an alternative to backup solution or by small and medium size of storage that we subscribe. The Cloud Based Peer-to-Peer Sharing Resources is a cloud based which will make use of existing open source technology. The technologies include PHP, HTML, CSS, MYSQL, and JAVA programming language. This system one of the applications to help the user to share file in cloud and chat with peers in peer to peer manner. Agile Modelling prototyping methodology has been used for completing this project. This application will serve as a medium for interaction between peers or user.